The dark side of relationship pursuit from attraction to obsession and stalking - Spitzberg, Brian H.; Cupach, William R. (Routledge/Taylor & Francis Group, 2014)
"The Dark Side of Relationship Pursuit provides historical and definitional frames for studying unwanted relationship pursuit, and considers the roles of media, law, and social science research in shaping today's conceptualizations of stalking. The volume integrates research for diverse contributing fields and disciplines, providing a through summary and assessment of current knowledge on stalking and obsessive pursuit."--Back cover.